Filsafat Sosial dalam Filsafat Islam Kontemporer: Wacana Masyarakat Madani dan Kontribusinya pada Filsafat Pendidikan - M. Abdul Fattah Santoso (Universitas Darussalam Gontor, 2014)
The presence of madani society discourse in the Muslim world in the last of 20th century and the beginning of 21st century has fulfilled the minimum of the study of social philosophy in Islamic Philosophy. This phenomenon has brought research questions: what is a madani society and what is its contribution to the philosophy of education. Through a historical research, the data has collected using documents and has analyzed using domain and reflective analysis. The research has found that madani society is the opposite of barbaric and primitive society, and not the opposite of religious society, responsible to build social order and defend public interests, and based on some basic values: civility, respect of differences, peaceful management of conflict and social control, autonomy and self-regulating, and social solidarity. Based on such values, social relations in ‘madani society’ are conducted by respecting the individual and communal rights, respecting egalitarianism and improvement of human dignity, living together fully tolerant and solid, respecting difference and managing peacefully conflict with dialogue, without truth claim and discrimination, controlling public administration and maintaining accountable government, and regulating trans ethnic public affairs with autonomy and self-reliance through rules and conventions. Moreover, the discourse contribution to the philosophy of education is that the nature of education is transmitting basic Islamic values to the society members in order to develop as Muslim civilized society who is also responsible to build an autonomous social order and defend public interests, full of solidarity.